Inovasi Birokrasi dan Optimalisasi Pelayanan Publik: Belajar dari Jembrana, Bali - Lendong, Romanus Ndau (Humaniora, 2010)
Jembrana Regency is placed strategically to keep Bali existence as a building of culture and civilization. Tribe and religious diversity cause Jembrana to be viewed as ’another Bali’, that is a more dynamic and compromising Bali. The current Jembrana is now mesmerizing after less than ten years in self renovation. This article will talk about how strategic bureaucratic innovation in optimalization of public service. Free education and health care policy, that are run consistently by Jembrana’s municipal government, become its frontliner in reaching Millenium Development Goals (MDGs) target. Prof. Dr. I Gede Winasa, former regent of Jembrana, is the main character behind this success. His background as academician and expanded relations from international fund organizations are his crusial ammunition to actualize his obsession absolving Jembrana from poverty, stupidity, and backwardness. Among what happens to this country, Jembrana’s breakthrough is worthy to be adopted in other areas in this country.